Adding Organic Matter Enhanced the Effectiveness of Silicate Rock Fertilizer for Food Crops Grown on Nutritionally Disorder Soils: A Glasshouse Assessment - Priyono, Joko; Arifin, Zaenal (JOURNAL OF TROPICAL SOILS, 2012)
A glasshouse experiment was carried to identify effects of the application rate of ground silicate rock as a multinutrientfertilizer (SRF) with and without organic matter (OM) on growth and nutrient status of food crops (rice,corn, and soybean). Those crops were grown on 3 different soils in 2 cropping patterns, i.e., rice – soybean and corn– soybean, providing 6 experimental sets. A completely randomized design was applied in each experimental set.The treatment in each set consisted of 3 rates of SRF (5, 10, and 15 g kg-1), those 3 rates + 5 g kg-1 of OM, and acontrol (without adding SRF or OM). The first crops (rice and corn) were grown up to 65 days, while the secondcrop (soybean) was up to 40 days. Results indicated that for crops grown on less fertile soils, the application of SRFonly slightly increased growth of crops, mainly of the 2nd crops, and adding OM greatly increased the growth ofboth the 1st and 2nd crops. In those experimental sets, about 60 – 80% of the variation of crop growth was significantlydetermined by concentration of Cu and several other essential nutrients in crop tissue. In contrast, the growth forcrops grown on more fertile soils was not affected by the application of SRF or/and OM. It was concluded thatadding OM enhanced the effectiveness of SRF as a multi-nutrient fertilizer, and that may be used as an appropriatemulti-nutrient fertilizer or general ameliorant to sustain soil quality and remediate the nutritionally disorder soils.